Ideas of Vladas Mačys About Civil Procedure Law in the Book “Lecture on Civil Procedure” - Bolzanas, Darius; Jokubauskas, Remigijus (Teisė, 2025)
The article examines the ideas of civil process presented a century ago in the book “Lectures of Civil Process” by Vladas Mačys and their significance for the development of the modern civil process. The article evaluates the model of the civil process proposed by Vladas Mačys, its main directions and relevance in the modern civil process. The article also evaluates which ideas of Vladas Mačys remained significant in the current civil proceedings and how the right to a fair trial could be ensured. The article aims to reveal the innovative ideas of the book “Lectures of Civil Procedure” that are significant for the development of the modern civil procedure.